Influence of Using Games on Learning English Vocabulary by Syrian Refugee Students in Jordan - Bader, Yousef F.; Razzaq, Diana Abdel (International Journal of Linguistics, 2021)
This study examines the influence of using games on learning English vocabulary and attempts to reveal the significant differences between using games and using traditional methods in learning English vocabulary among sixth grade Syrian students in Jordan. For these purposes, a group of thirty female participants were divided into two groups, each one consisting of fifteen participants. The first group was exposed to forty minutes of ten vocabulary games, three days a week for four months. The second group was exposed to traditional methods in learning vocabulary for forty minutes a day, three days a week for four months. The latter method depended on the teacher’s role in giving words and their meaning, writing them on the board and asking students to memorize them. The researchers selected certain vocabulary games according to several criteria to be given to children. A pretest was conducted for each group to compare its results with the posttest results. The results of the comparison showed a significant increase in participants’ accomplishment by using vocabulary games. This suggests that vocabulary games can be used as an effective tool in learning English vocabulary.